2000
DOI: 10.1126/science.290.5489.138
|View full text |Cite
|
Sign up to set email alerts
|

Proximity of Chromosomal Loci That Participate in Radiation-Induced Rearrangements in Human Cells

Abstract: Rearrangements involving the RET gene are common in radiation-associated papillary thyroid cancer (PTC). The RET/PTC1 type of rearrangement is an inversion of chromosome 10 mediated by illegitimate recombination between the RET and the H4 genes, which are 30 megabases apart. Here we ask whether despite the great linear distance between them, RET and H4 recombination might be promoted by their proximity in the nucleus. We used two-color fluorescence in situ hybridization and three-dimensional microscopy to map … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
237
0
13

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(262 citation statements)
references
References 19 publications
(7 reference statements)
12
237
0
13
Order By: Relevance
“…It has been shown that RET translocation partners like the H4 gene are in close spatial continuity during interphase. With radiation induced breakage enabling rearrangement between RET and H4, this results in the RET/PTC1 fusion gene seen in R-PTC [14]. A similar mechanism is possible with MASC, where the ETV6-NTRK3 fusion product is the result of similar spatial continuity during interphase.…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that RET translocation partners like the H4 gene are in close spatial continuity during interphase. With radiation induced breakage enabling rearrangement between RET and H4, this results in the RET/PTC1 fusion gene seen in R-PTC [14]. A similar mechanism is possible with MASC, where the ETV6-NTRK3 fusion product is the result of similar spatial continuity during interphase.…”
Section: Discussionmentioning
confidence: 96%
“…Cells in which there was only one signal were excluded from analysis to avoid any artefacts owing to section preparation. In an earlier study, it has been demonstrated that in 35% of normal human thyroid cells at least one pair of RET and H4 signals were juxtaposed detected by FISH analysis (Nikiforova et al, 2000). Thus, a significant number of tumour cells with RET/PTC rearrangement might be misclassified, which is dependent on the interphase arrangement of chromosome 10 in the tumour nuclei and the linear distance between RET and the partner gene.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid this problem, we have used in our study a different FISH approach showing overlapping FISH signals in normal nuclei and split signals only when the RET gene is disturbed. This approach avoids confusion caused by the interphase arrangements of chromosome 10 as described by Nikiforova et al (2000). We also have performed a series of control studies that argue against artefacts (caused by the nuclear arrangement of chromosome 10 or by formalin fixation).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the frequency of observed recurrent gene fusions arising from translocations in cancer cells correlates with the frequency of side-by-side pairing of the relevant genes in normal control cells. These include BCR and ABL (fused in chronic myeloid leukaemia); PML and RARA (acute promyelocytic leukaemia); MYC and IGH, IGK or IGL (B cell leukaemia/lymphoma); IGH and CCND1, BCL2 or BCL6 (B cell leukaemia/lymphoma) [43][44][45][46][47][48].…”
Section: Generation Of Chromosome Rearrangementsmentioning
confidence: 99%